2021
DOI: 10.1177/02698811211029752
|View full text |Cite
|
Sign up to set email alerts
|

Increasing dietary choline attenuates spatial memory deficits resulting from exposure to the chemotherapeutic agents cyclophosphamide and doxorubicin

Abstract: Background: Choline supplementation (+Ch) improves cognitive function in impaired animals and humans. Chemotherapy-related cognitive deficits (CRCDs) occur in cancer patients, and these deficits persist following treatment, adversely impacting quality of life. To date, there are no approved treatments for this condition. Aim: Because +Ch improves impaired memory, it was of interest to determine whether +Ch can attenuate spatial memory deficits induced by the chemotherapeutic agents doxorubicin (DOX) and cyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…The results of the reversal test proved that highly anxious mice can learn the water maze task, but they require a longer training to initiate searching in the center of the maze. Occurrence of highly anxious BALB/c mice that predominantly float has been reported by others (Francis et al, 1995;Johns et al, 2021;Philpot et al, 2016;Wahlsten et al, 2005). In some studies, such mice were excluded from testing.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of the reversal test proved that highly anxious mice can learn the water maze task, but they require a longer training to initiate searching in the center of the maze. Occurrence of highly anxious BALB/c mice that predominantly float has been reported by others (Francis et al, 1995;Johns et al, 2021;Philpot et al, 2016;Wahlsten et al, 2005). In some studies, such mice were excluded from testing.…”
Section: Discussionmentioning
confidence: 94%
“…In some studies, such mice were excluded from testing. One study (Philpot et al, 2016) described removal from the study of 13 of 38 females, and 1 of 18 males, and other (Johns et al, 2021) described removal of 16 of 50 females. In those studies, water was kept at 24 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Choline, a strong organic base and a constituent of lecithin, is widely added to human food and animal feed to ensure the health of humans and animals and improve the production performance of livestock and poultry. It is present in sphingomyelin and is a precursor of the neurotransmitter acetylcholine 22 . As a neurotransmitter, acetylcholine's increase can speed up the transmission of information and increase the brain's activity 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Moreno et al found that prenatal choline supplementation could accelerate the development of long‐term memory in offspring rats 27 . Moreover, Johns et al reported that choline supplementation alleviated chemotherapeutic‐induced spatial memory deficits 22 . Lots of studies have confirmed the toxic effects of fluoride on the offspring's nervous system and learning and memory ability 15,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Johns and colleagues' report findings that support the use of Choline supplementation (+Ch) as an intervention for chemotherapy-related cognitive deficits and suggest that impairments of hippocampal-mediated cognitive function following exposure to chemotherapeutic agents, doxorubicin and cyclophosphamide may be the result of altered cholinergic function (Johns et al, 2021). They recommend that further studies are necessary to determine if +Ch provides similar benefits in individuals with tumours, and importantly, whether +Ch contributes to tumour development and growth or adversely impacts the effectiveness of chemotherapy.…”
mentioning
confidence: 99%